The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10072-015-2299-6
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the INECO frontal screening (IFS) in the detection of executive dysfunction in patients with relapsing-remitting multiple sclerosis (RRMS)

Abstract: Several studies have reported that about 65 % of patients with relapsing-remitting multiple sclerosis (RRMS) suffer from cognitive impairment, with executive dysfunction being the most frequently described. Even if several executive screening tests have been designed to specifically detect executive deficits, few studies have investigated their ability to tackle such dysfunction particularly in multiple sclerosis (MS). The aim of the present study was to evaluate the sensitivity and specificity of the INECO fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…The IFS was designed to include several subtests in order to measure, in an efficient way, as many EF as possible. Previous studies have shown promising diagnostic performance [6] , [7] , [8] , [9] , [10] . Thus, it arises as an encouraging alternative for early detection of dementia cases.…”
Section: Introductionmentioning
confidence: 99%
“…The IFS was designed to include several subtests in order to measure, in an efficient way, as many EF as possible. Previous studies have shown promising diagnostic performance [6] , [7] , [8] , [9] , [10] . Thus, it arises as an encouraging alternative for early detection of dementia cases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, IFS is a brief neuropsychological test designed to explore executive functions across neurodegenerative pathologies such as AD, 13 behavioral variant frontotemporal dementia, 14 Multiple Sclerosis (relapsing-remitting phase), 15 MCI, 16 and MCI in Parkinson's disease. 17 IFS is composed of eight subtests, organized into three main executive domains: 18 1) inhibition and change, 2) working memory, and 3) capacity for abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados coinciden con las investigaciones en casos clínicos; en este sentido, el estudio de pacientes con demencia realizado por Manes y su grupo obtuvo un corte de 25 puntos, con una sensibilidad del 96.2% y especificidad del 91.5%; y un área bajo la curva de 0.98 (Torralva, Roca, Gleichgerrcht, López et al, 2009). De manera similar el estudio desarrollado por Bruno y colaboradores, el uso del IFS en pacientes con esclerosis múltiple obtuvo un punto de corte de 25.5, con una sensibilidad del 73.53% y especificidad del 78.13%; con una área bajo la curva de 0.85 (Bruno et al, 2015).…”
Section: Discussionunclassified